Cross-border prudential policy spillovers: How much? How important? Evidence from the international banking research network - Claudia M. Buch; Linda Goldberg (Deutsche Bundesbank, 2017)
The development of macroprudential policy tools has been one of the most significant changes in banking regulation in recent years. In this multi-study initiative of the International Banking Research Network (IBRN), researchers from 15 central banks and 2 international organizations use micro-banking data in conjunction with a novel dataset of prudential instruments to study international spillovers of prudential policy changes for bank lending growth. The collective analysis has three main findings. First, prudential instrument effects sometimes spill over across borders through bank lending. Second, international spillovers vary across prudential instruments and are heterogeneous across banks. Bank-specific factors like balance sheet conditions and business models drive the amplitude and direction of spillovers to lending growth rates. Third, international spillovers of prudential policy on loan growth rates have not been large on average. However, our results tend to underestimate the full effect by focusing on adjustment along the intensive margin and by analyzing a period in which relatively few countries implemented country-specific macroprudential policies.
Keywords: G01; F34; G21; 330; international banking; macroprudential; regulation; spillovers; lending